IMPLEMENTASI PORTAL JAKARTA OPEN DATA DALAM MENDUKUNG PEMBANGUNAN BERKELANJUTAN - Samsul Ode; Firman Firman; Fuad Syahrudin; Surya Yudha Regif (Jurnal Kebijakan Publik, 2022)
This paper is the result of research on the implementation of the Jakarta Open Data portal in supporting sustainable development in DKI Jakarta. The approach in this study used descriptive qualitative methods to provide a clear picture of the problems studied, identify and explain the existing data systematically. The main theory used in this research is the Van Meter and Horn implementation theory with its indicators and the theory of open government, open data and sustainable development as supporting theories. The results show that the implementation of the Jakarta Open Data portal as a portal that provides data information generated from regional apparatus organizations in the DKI Jakarta Province has been going quite well because it makes it easier for people to find and access data information. Utilization of data on the Jakarta Open Data portal can open up space for public participation and input for the DKI Jakarta Provincial Government in improving governance and supporting sustainable development in the realm of public information disclosure. However, there are still obstacles because regional apparatus organizations that have data and information officers in the process of managing data in their work units that will be uploaded to the Jakarta Open Data portal system are not yet optimal, causing inequality in the data presented in each regional apparatus organization and affecting the availability of collections data on the Jakarta Open Data portal.Keywords: Jakarta Open Data Portal, Implementation, Open Government and Sustainable Development.